Psychology essentials - Santrock, John W. (McGraw-Hill, 2003)
Success is in the balance. In the second edition of "Essentials of Psychology", John Santrock presents the perfect balance of big ideas vs. supporting detail, breadth vs. depth, and research vs. application all wrapped in a pedagogical system that effectively guides the student through the key concepts of psychology. New learning goals launch each chapter and serve as the organizing mechanism for the text and supporting materials. These learning goals focus students' attention on the big ideas of psychology. Rich applications and current research support the big ideas so that students emerge with an understanding of the key concepts, not a collection of supporting detail. Your success and your students' success is in the Balance, Santrock provides you with the balance you need to succeed. The "Essentials" edition was developed to satisfy the demand for a shorter text that could easily be covered in one semester. The chapters were rewritten to maintain the continuity and pedagogy that has made Santrock a student and market favorite. Thinking, Language, and Intelligence have been combined to form one cohesive chapter and the health psychology and statistics coverage has been moved into an appendix.